Modelling Based Analysis and Optimization of Simultaneous Saccharification and Fermentation for the Production of Lignocellulosic-Based Xylitol - Ibnu Maulana Hidayatullah; I G B N Makertihartha; Tjandra Setiadi; Made Tri Ari Penia Kresnowati (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Simultaneous saccharification and fermentation (SSF) configuration offers efficient use of the reactor. In this configuration, both hydrolysis and fermentation processes are conducted simultaneously in a single bioreactor, and the overall processes may be accelerated. However, problems may arise if both processes have different optimum conditions, and therefore process optimization is required. This paper presents a mathematical model over SSF strategy implementation for producing xylitol from the hemicellulose component of lignocellulosic materials. The model comprises the hydrolysis of hemicellulose and the fermentation of hydrolysate into xylitol. The model was simulated for various process temperatures, prior hydrolysis time, and inoculum concentration. Simulation of the developed kinetics model shows that the optimum SSF temperature is 36 °C, whereas conducting prior hydrolysis at its optimum hydrolysis temperature will further shorten the processing time and increase the xylitol productivity. On the other hand, increasing the inoculum size will shorten the processing time further. For an initial xylan concentration of 100 g/L, the best condition is obtained by performing 21-hour prior hydrolysis at 60 °C, followed by SSF at 36 °C by adding 2.0 g/L inoculum, giving 46.27 g/L xylitol within 77 hours of total processing time. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).